Union Mergers - Graham, Harry (Relations industrielles / Industrial Relations, 1970)
The author stresses the importance of reexamining the structure of the American labor movement, which has to face changing economic and social conditions, and depicts the main difficulties which hinder changes in the actual system. His line of study bears specifically on the possibility of union mergers, which seems to be the most practical solution to the present structural inadequacies in unionism.